The ideological origins of the American Revolution - Bailyn, Bernard (Cambridge : The Belknap, 1967)
The Ideological Origins of the American Revolution is a classic of American historical literature--required reading for understanding the Founders' ideas and their struggles to implement them. In the preface to this 50th anniversary edition, Bernard Bailyn isolates the Founders' profound concern with the uses and misuses of power.--
The literature of revolution -- Sources and traditions -- Power and liberty: a theory of politics -- The logic of rebellion : a note on conspiracy -- Transformation -- Representation and consent -- Constitution and rights -- Sovereignty -- The contagion of liberty -- Slavery -- Establishment of religion -- The democracy unleashed -- "Whether some degree of respect be not always due from inferiors to superiors".
Includes bibliographical references and index.
Keywords: Political science -- United States